Hierarchical mesoscale assembly of PbO(2)on 3D titanium felt/TiO2 nanotubular array electrode for anodic decolourisation of RB-5 dye - Harito, C.; Zaidi, S. Z. J.; Bavykin, D.; Martins, A. S. [UNESP]; Yuliarto, B.; Walsh, F. C.; Leon, C. Ponce de (Iop Publishing Ltd, 2020)
Hierarchical PbO(2)nanoparticles (NPs) were grown by hydrothermal method on TiO(2)nanotubes (NTs) at 3D titanium felt, which is simple and scalable method. TiO2NTs were formed on titanium felt by anodising at 25 degrees C in environmentally friendly methanesulphonic acid solution. The growth of PbO(2)on the TiO2NTs depended on immersion time during hydrothermal synthesis and followed a LaMer-Dinegar burst kinetic model of nucleation and growth. PbO(2)formation began with rapid nucleation, followed by mesoscale assembly due to organic capping of poly(vinylpyrrolidinone). The electrochemical performance of 3D electrode was recorded in pH 3 sodium sulphate solutions containing Reactive Black 5 (RB-5) azo dye at 25 degrees C. The resulting hierarchical 3D electrode achieved 98% decolourisation after 50 min of anodic oxidation with a first order batch decay rate of 0.0875 min(-1).
Keywords: 3D electrode; electrocatalyst; hierarchical; lead dioxide; TiO2 nanotube